2010
DOI: 10.3155/1047-3289.60.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Volatile Organic Compounds in the Vicinity of an Optoelectronics Industrial Park in Taiwan

Abstract: This study aimed to determine the concentration of volatile organic compounds (VOCs) and investigate the impacts of traffic and industrial activities on the concentration of VOCs near the Central Taiwan Science Park (CTSP) in Taiwan during 2005. Twelve-hour canister sampling was performed at 10 sites near CTSP every season. Samples were analyzed by gas chromatography with a mass-selective detector. The traffic flow rate, industrial production rates, and meteorological information were also collected to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The detection limits of the analyzed VOCs ranged from 0.4 g m −3 (ethanol) to 0.9 g m −3 (PGMEA), and the recovery rates of all VOCs were between 96.2% (acetone) and 101.1% (m/p-xylene), with relative standard deviations ranging from 1.4% (PGMEA) to 7.0% (acetone). Details of the operational conditions of the gas-chromatograph/mass spectrometry system, VOC analyses, and QA/QC procedures have been described in a previous study [5]. According to the environmental concentrations of VOCs measured at work, each subject was classified into 1 of 20 workstations with other subjects exposed to similar amounts of VOCs.…”
Section: Volatile Organic Compounds Exposure Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection limits of the analyzed VOCs ranged from 0.4 g m −3 (ethanol) to 0.9 g m −3 (PGMEA), and the recovery rates of all VOCs were between 96.2% (acetone) and 101.1% (m/p-xylene), with relative standard deviations ranging from 1.4% (PGMEA) to 7.0% (acetone). Details of the operational conditions of the gas-chromatograph/mass spectrometry system, VOC analyses, and QA/QC procedures have been described in a previous study [5]. According to the environmental concentrations of VOCs measured at work, each subject was classified into 1 of 20 workstations with other subjects exposed to similar amounts of VOCs.…”
Section: Volatile Organic Compounds Exposure Assessmentmentioning
confidence: 99%
“…Finally, the module assembly process involves connecting additional components such as driver-integrated circuits and backlight units to the fabricated glass panel. A variety of VOCs has been reported to be emitted in these processes, including acetone, ethanol, ethyl acetate, isopropyl alcohol, propylene glycol monomethyl ether (PGME), propylene glycol monomethyl ether acetate (PGMEA) and toluene [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…For each collected canister sample, analyzed compounds were determined partly based on the safety data sheets (SDS) provided by the safety and health personnel of the industry, and some were by reference to researches related to this industry (Hsieh et al, 2005;Lin et al, 2013a, b;Chang et al, 2010b;Yang et al, 2016). As a result, a total of 107 VOCs were included for sample analyses.…”
Section: Analyzing For Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
“…In a liquid crystal display (LCD) manufacturing factory, longterm exposures to multiple chemicals of low levels might lead to premenopausal female workers with modest changes in their reproductive hormone urinary concentrations (Lin et al, 2013b;Chan et al, 2017). A slightly increase in kidney dysfunction risk was identified for workers in a TFT-LCD industry (simultaneously exposed to IPA, PGMEA, and propylene glycol monomethyl ether (PGME)) with their total exposure levels ≥ 50 ppb for 3-5 years (Chang et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have reported detailed air quality data collected in high-tech industrial parks (i.e., the electronics and biotechnology industries). [2,3,5,6] However, VOCs and acid/base gas pollutants of optoelectronics systems and components have received little attention despite the use of many chemicals that contribute to the above pollutants. For example, isopropanol (IPA) and acetone are used as cleaners; tetra-methyl-ammonium hydroxide (TMAH) and tris-(2-maleimidoethyl amine (TMEA) are used as developers; dimethyl sulfoxide (DMSO), 2-methylaminoethanol (MEA), butyl diglycol (BDG) and N-methyl pyrrolidinone (NMP) are used as strippers; and propylene glycol monomethyl ether (PGME) and propylene glycol monomethyl ether acetate (PGMEA) are used to clean photo-resist nozzles.…”
Section: Introductionmentioning
confidence: 99%